PENERAPAN VARIASI TEKNIK BERTANYA PADA PEMBELAJARAN MATERI GETARAN DI KELAS VIII SMP - Nurmala yarso; Tomo Djudin; Syaiful B Arsyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study aims to determine the effectiveness of the questioning variation techniques application to improve VIII grade students learning outcome about vibration in SMP Negeri 2 Sungai Raya. The research method used is experimental research method in Pre-experimental design form with one group pretest-posttest design model. 33 students from class VIII as the sample of this research taken by intact group technique. The instrument in this study was a test of learning outcomes, consisting of 15 multiple choice questions with open reason. The results of the analysis of pretest and posttest learning outcomes show an increase in learning outcomes as evidenced by a change of 27.45%. There is a significant difference between the pretest and posttest learning outcomes. The effect size of the questioning variation techniques application is 2,91 (high category). The questioning variations technique application was effecive to improve student learning outcomes. The results of this study expected to be an alternative in an effort to improve student learning outcomes about vibration. Keywords: Application, Learning Outcomes, Questioning Techniques Variations, Vibration